Mediation services in the educational system: skills' formation of interpersonal relations' culture - Kulsharipova, Z.K.; Syrymbetova, L.S.; Zhakubaldina, B.B.; Kenzhebaeva, Zh.T. (KU publ., 2020)
In the modern world, the mediation process is becoming increasingly relevant every day. After all, modern society is full of stresses, which subsequently leads to conflicts and disputes. In most cases, intermediaries can help solve problems. School mediation is the cure for bullying. All adults want their children to be successful, independent and happy. They want the children to live between friendly and interesting people and help each other. So that children can avoid war and violence. So, they feel safe. Live not in the battle for a «place in the sun», but in creativity and creativity. The purpose of the reconciliation service is to create favorable conditions for resolving conflicts without prejudice to participants in the educational process, improving the safety of the school environment and the use of technologies that are safe for health. Mediation is one of the alternative dispute resolution technologies in which a third neutral mediator is involved who is not interested in the conflict and which helps the parties reach a concrete agreement on the dispute, while the parties have full control over the dispute. Decision making process. Settlement of a dispute and conditions for its resolution.
Білім беру жүйесіндегі медиация қызметі: тұлғааралық мəдениетті қалыптастыру
Службы медиации в образовательной системе: формирование навыков культуры межличностных отношений
Keywords: conflict in society; aggressive methods of interaction; school placement; competition; the conflicts; the school services model; the attitude of a group of classmates; cultural levels